Pilot Study Proposal - Eiselein, Gregory; Lehning, Emily (Kansas State University. K-State First., 2008)
A proposal which gives direction and suggestions on what should be done in the 2009 academic year for the new incoming students, sent to the First-Year Student Task Force. The proposal outlines a pilot study, comprised of 16 sections of 15 different courses in 12 academic departments housed in 6 different colleges.
Keywords: First-year experience program; Reports; Pilot study; Papers (document genres)